A Novel Sorbitol-Based Flow Cytometry Buffer Is Effective for Genome Size Estimation across a Cypriot Grapevine Collection - Michael, Kyriakos; Andreou, Constantina; Markou, Anastasia; Christoforou, Michalakis; Nikoloudakis, Nikolaos (My University, 2024)
Flow cytometry (FCM) is a widely used technique to study genome size (C-value), but recalcitrant metabolites in grapevines often hinder its efficiency in grapevine research. The aim of the present study was (i) to develop a novel buffer tailormade for the nuclei isolation of grapevines and (ii) to characterize a Cypriot germplasm collection based on C-values. A local cultivar "Xinisteri" was used as a pilot test to evaluate a Sorbitol-based buffer, while sprouting, young, and fully matured leaves were examined to evaluate the developmental parameter. The novel Sorbitol buffer was shown to have a coefficient of variation (CV) of 4.06%, indicating improved properties compared to other commonly used FCM buffers [WPB (7.69%), LB01 (6.69%), and LB (7.13%), respectively]. In addition, a significant variation in genome size between genotypes was found in a comprehensive application with 24 grape varieties. Nucleic content (2C) ranged from 0.577/1C pg for the "Assyrtiko" cultivar up to 0.597/1C pg for the "Spourtiko" cultivar, revealing a 17.6/1C Mbp difference. The lowest coefficient of variation (CV) across all entries was found in the variety "Ofthalmo" (2.29%), while the highest was observed in "Pinot Noir" (3.44%). Anova analysis revealed several distinct clusters, showing that in several cases, C-values can be used as a simple method to distinguish grapevine cultivars.
Keywords: C-value; DNA content; Sorbitol; Tannins; Vitis vinifera